Anti-oxidative Activity of Nepalese Traditional Anti-diabetic Medicines - Devkota, HP; Adhikari-Devkota, A; Yahara, S; Basnet, P (Nepal Journal of Science and Technology, 2014)
Chronic overproduction of free radicals in human body has a role in numerous disease states including diabetes. Proper use of antioxidants may help in the prevention and/or treatment of diabetes. For the management of diabetes, a combination of herbal drugs is being practiced traditionally in Nepal. These herbal medicines might have a good correlation to anti-oxidative properties. Anti-oxidative property was evaluated with the methanolic extracts of nineteen common traditional anti-diabetic medicines by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method. Among the evaluated herbal medicines, Phyllanthus emblica, Punica granatum, Syzygium cumini, Terminalia bellirica and Terminalia chebula showed potent radical scavenging activity. The activities of P. emblica, T. bellirica and T. chebula were more potent than that of ascorbic acid. Some of the reported popular hypoglycemic herbal drugs did not show strong activity. Therefore strong anti-oxidative herbal drugs in combination with hypoglycemic drugs might have better results in the management of diabetes. DOI: http://dx.doi.org/10.3126/njst.v14i2.10429 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 151-154